O-003 Predictors of successful revascularization in the ARISE II study. (22nd July 2019) - Jadhav, A; Desai, S; Liebeskind, D; Yoo, A; Bozorgchami, H; Ribo, M; Saver, JL; Mattle, H; Andersson, T; Zaidat, O
Abstract : Introduction: Swift and complete revascularization in large vessel occlusion (LVO) stroke is associated with better functional outcomes. First pass effect (FPE), achievement of TICI 2C/3 revascularization on the first pass, is a new metric of technical success of endovascular thrombectomy (EVT). We aim to identify predictors of FPE and TICI 3 revascularization in the ARISE II study. Methods: Anterior circulation LVO [ACLVO-internal carotid (ICA) and middle cerebral artery (MCA-M1)] strokes from the ARISE II study were used for this analysis. Core-lab adjudicated TICI scores after the first pass of EmboTrap were collected. FPE and modified FPE (mFPE) were defined as first pass achievement of TICI 2C/3 and TICI ≥2B, respectively. Demographic, clinical and radiographic parameters were analyzed. Multivariable logistic regression was performed to identify predictors. Results: A total of 161 ACLVOs underwent thrombectomy in the ARISE II study. Mean age was 67 ±13 years and 43% (n=69) were male. Mean NIHSS and median ASPECTS were 16 ±5 and 10, respectively. While FPE was achieved in 37% (n=59), mFPE was seen 43% (n=69) patients. Multivariable logistic regression was performed using age, sex, use of IV-tpA, BMI, NIHSS, vascular risk factors, ASPECTS, collateral status (ASITN), occlusion location and use of balloon-guided catheter as variables. While absence of ICA occlusion (p=0.07, OR-8.6, 0.8–90) can predict FPE, there were no independent predictors of mFPE. Independent predictors of TICI 3 after 3 passes include use of balloon guide catheter (p=0.01, OR-0.033, 0.003–0.535) and higher ASITN score(p=0.04, OR-10.2, 1–100). Conclusion: Absence of internal carotid artery occlusion predicts FPE and the use of balloon guide catheter and favorable collaterals predicts complete revascularization. These results support the consideration of routine BGC use with the Embotrap device to achieve complete revascularization. Disclosures: A. Jadhav: None. S. Desai: None. D. Liebeskind: None. A. Yoo: None. H. Bozorgchami: None. M. Ribo: None. J. L: None. H. Mattle: None. T. Andersson: None. O. Zaidat: None.